Sulfonated polystyrenes: pH and Mg2+-insensitive amphiphilic copolymers for detergent-free membrane protein isolation - Janata, Miroslav; Gupta, Sachin; Čadová, Eva; Angelisová, Pavla; Krishnarjuna, Bankala; Ramamoorthy, Ayyalusamy; Hořejší, Václav; Raus, Vladimír (European polymer journal, 2023)
Amphiphilic polymers are increasingly applied in the detergent-free isolation and functional studies of membrane proteins. However, the carboxylate group present in the structure of many popular variants, such as styrene-maleic acid (SMA) copolymers, brings limitations in terms of polymer sensitivity to precipitation at acidic pH or in the presence of divalent metal cations. Herein, we addressed this problem by replacing carboxylate with the more acidic sulfonate groups. To this end, we synthesized a library of amphiphilic poly[styrene-co-(sodium 4-styrene sulfonate)] copolymers (termed SSS), differing in their molecular weight and overall polarity. Using model cell membranes (Jurkat), we identified two copolymer compositions (SSS-L30 and SSS-L36) that solubilized membranes to an extent similar to SMA. Interestingly, the density gradient ultracentrifugation/SDS-PAGE/Western blotting analysis of cell lysates revealed a distribution of studied membrane proteins in the gradient fractions that was different than for SMA-solubilized membranes. Importantly, unlike SMA, the SSS copolymers remained soluble at low pH and in the presence of Mg2+ ions. Additionally, the solubilization of DMPC liposomes by the lead materials was studied by turbidimetry, DLS, SEC, and high-resolution NMR, revealing, for SSS-L36, the formation of stable particles (nanodiscs), facilitated by the direct hydrophobic interaction of the copolymer phenyls with lipid acyl chains.
Keywords: solubilization; amphiphilic copolymer; sulfonated polystyrene; membrane protein; cell membrane